Comparison of clinical outcomes between flexible antagonist protocol and long luteal phase protocol in patients with normal ovarian reserve function: a prospective cohort study - Tian, Ying; Hao, Jing; Tu, Xueliang; Feng, Shaobin; Li, Mingtao; Chen, Yang; Cao, Zelei (Frontiers in Endocrinology, 2025)
ObjectiveOvarian stimulation protocols play a pivotal role in the success of in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) treatments. This study compares the clinical outcomes of the long luteal phase GnRH agonist protocol and the flexible GnRH antagonist protocol in patients with normal ovarian reserve.MethodsThis prospective cohort study was conducted at the Reproductive Medicine Center, Sanmenxia Hospital, Yellow River, from March 2021 to September 2023. Patients with normal ovarian reserve were enrolled and randomly assigned by a 1:3 ratio to either the long luteal phase protocol (Group A, n=42) or the flexible antagonist protocol (Group B, n=118). Data on patient characteristics, ovarian response, and embryological outcomes were collected and analyzed. Clinical outcomes, including clinical pregnancy, live birth rates, and ovarian hyperstimulation syndrome (OHSS) incidence, were assessed. Multivariate logistic regression was conducted to identify risk factors associated with clinical pregnancy.ResultsThere were no significant differences in baseline characteristics between the two groups (P>0.05). In terms of primary clinical outcomes, there were no significant differences in clinical pregnancy rate (54.8% vs. 56.8%, P=0.092), live birth rate (47.6% vs. 52.5%, P=0.278), or incidence of OHSS (0% vs. 2.5%, P=0.055) between Group A and Group B. Multivariable logistic regression analysis identified significant predictors of clinical pregnancy, including younger age (OR = 0.956, P = 0.042), higher AFC (OR = 1.127, P = 0.018), higher AMH levels (OR = 1.357, P = 0.005), greater endometrial thickness (OR = 1.162, P = 0.021), higher number of oocytes retrieved (OR = 1.234, P = 0.023), and better embryo quality (Grade I-II) (OR = 1.485, P = 0.002). No significant differences were observed between age-related subgroups (P>0.05), but success rates decreased with increasing age, highlighting age as a key factor influencing IVF/ICSI outcomes.ConclusionThe study found no significant differences in primary clinical outcomes between the two groups. However, younger age, higher AFC, higher AMH levels, greater endometrial thickness, higher number of oocytes retrieved, and better embryo quality were significant predictors of clinical pregnancy.